2005
DOI: 10.1001/archopht.123.8.1149
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Infarction Following Photodynamic Therapy With Verteporfin

Abstract: 1. Sieving PA, Niffennegger JH, Berson EL. Electroretinographic findings in selected pedigrees with choroideremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 5 publications
1
33
0
1
Order By: Relevance
“…Although we cannot exclude some masking effects of soft drusen and Bruch's membrane deposits, clinicians should be aware of the circulatory abnormalities that persisted until the late phase of ICGA, especially when considering treatment. PDT with verteporfin might be reconsidered, because it can severely impair the already compromised choriocapillaris in the macula [11]. Further studies with a large number of patients, and comparisons with conventional ARMD, are needed to determine the precise relationship between choroidal circulatory disturbances and RAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we cannot exclude some masking effects of soft drusen and Bruch's membrane deposits, clinicians should be aware of the circulatory abnormalities that persisted until the late phase of ICGA, especially when considering treatment. PDT with verteporfin might be reconsidered, because it can severely impair the already compromised choriocapillaris in the macula [11]. Further studies with a large number of patients, and comparisons with conventional ARMD, are needed to determine the precise relationship between choroidal circulatory disturbances and RAP.…”
Section: Discussionmentioning
confidence: 99%
“…Two eyes with stage 2 RAP and pigment epithelial detachment (PED) underwent photodynamic therapy (PDT) with verteporfin, which treated the areas covering the entire PEDs. Because PDT can cause persistent choroidal ischemia [11], these eyes were excluded from the evaluation of the choroidal circulation. The study group ultimately included 19 eyes (11 eyes with stage 1 or stage 2 RAP and eight fellow eyes without RAP).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the collateral hypofluorescence that occurs after PDT reaches its maximum 1 week after the treatment, and is then reduced in size and intensity over time [3]. Rare complications of PDT for CNV include occlusions of deep choroidal vessels, ischemia and choroidal infarction [4].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported that hypofluroscence after PDT is associated with the occlusion of the choriocapillaris and swelling in the adjacent retinal pigment epithelium [2]. Recently, half-dose PDT has been proposed as an effective therapeutic option for chronic CSCR to prevent retinal pigment epithelium or choriocapillaris damage [3].…”
Section: Dear Editormentioning
confidence: 99%